Evolution of the management paradigm of construction enterprises - Onofriichuk , O. (Ways to Improve Construction Efficiency, 2022)
The article substantiates the need to shift from industrial–resource-based approaches to managing construction enterprises toward digital, stakeholder-oriented, and biosphere-compatible models in response to the climate, resource, and regulatory challenges of the twenty-first century. The study design combines systems-evolutionary and comparative-institutional analysis, a morphological comparison of paradigms by the criteria of management philosophy, resource factors, the role of technologies, stakeholder interaction, and socio-ecological orientations, as well as benchmarking of global practices in the EU, the United States, and Asian countries. The sequence of transformations is shown: from the industrial–resource paradigm, through the innovation-technological and the digital-stakeholder paradigms, to the biosphere-compatible ecosystem paradigm in which decisions rely on integrated economic, social, and climate indicators. The European model institutionalizes requirements through common indicators and reference architectures of digital platforms; the American model emphasizes industrialization, AI-driven risk management, and market-based “green” standards; Asian jurisdictions scale state programs for the digitalization and robotization of production–construction processes. Practical guidelines for Ukrainian enterprises include the deployment of a common data environment and data-governance policies with a phased transition to BIM Level 3; the formation of inter-organizational Data Spaces for the sovereign exchange of verified data; the institutionalization of ESG reporting and the unification of LCA/LCC; procurement and contracting reform toward integrated collaboration models with payment based on life-cycle performance; the scaling of modular off-site construction; and the development of competencies in BIM/IDM, sustainability assessment, and risk analytics. A transition roadmap is proposed with intermediate milestones—from BIM Level 2 to Level 3, from local CDEs to inter-organizational Data Spaces—and performance indicators including carbon budgets, supply-chain transparency, and the share of reused materials, ensuring alignment of economic efficiency with climate neutrality and the social legitimacy of construction project.